The impact of the progressive movement on the domestic politics of US President Theodore Roosevelt (1901 - 1908) - Maleh, Ass.Lec Khaled Razak (Thi Qar Arts Journal, 2022)
The progressive movement appeared in the United States of America in the nineties of the nineteenth century and extended to the twenties of the twentieth century, and it represented a reform revolution on the economic and social conditions that prevailed in American society at the time, which resulted in class inequality through which a class of the wealthy and domineering over the working class and the poor emerged, The methods of expression and activities pursued by the supporters of the progressive movement since its inception varied, including writing books and writing articles that focused on the bad economic and social conditions, as well as the emergence of investigative journalism that worked to expose scandals and violations against the poor and workers in cities and large factories, in addition to That is why some have formed unions and clubs that support the rights of workers, women, children, the middle class and the poor alike. When Theodore Roosevelt came to power in 1901, the progressives felt that they could implement their own reform policies due to the harmony and compatibility between him and their orientations. That president is the way for the progressive movement to establish its presence and achieve some of its aspirations.